Tingkat Intensitas Penggunaan Uang Digital pada Masyarakat di Kota Dumai - Irma Nuriana; Dyah Faradhila; Clara Rizky Irwana; Novi Aulia Ardana; Hildawati Hildawati (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This research aims to measure the intensity of digital currency use among the people of Dumai City. The development of non-cash payment technologies such as QRIS, e-wallets, and mobile banking has changed the way people conduct daily transactions. This study employed a descriptive quantitative, with data collected through a questionnaire involving 40 respondents, the majority of whom were aged 17–25 and students. The results show that the use of digital currency in Dumai City is quite well known and implemented in daily activities, although it has not completely replaced cash. QRIS is the most widely used application compared to e-wallets and mobile banking. The majority of respondents expressed neutral to positive responses regarding the intensity of use, types of transactions, comparison with cash, location of use, and reasons for using digital currency. Overall, digital currency has been accepted as a practical and efficient payment alternative, but there is still a need for increased use and equal access to digital payment systems so that the digital payment system can be utilized more optimally.